2015
DOI: 10.1556/004.2015.042
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and pain in dogs with early-stage mammary tumours

Abstract: Quality of life (QOL) was evaluated in bitches with mammary tumours (MTs) by applying a scale to assess QOL in dogs with pain secondary to cancer. Two groups were constituted: Group 1 with 80 bitches with MT, oncologically classified as stage I (mean age ± SD = 9.9 ± 3.8 years), and Group 2 consisting of 80 healthy bitches without MT (mean age: 7.7 ± 1.8 years). The results were based on responses from owners using a standardised, internationally accepted pain-scale questionnaire. This prospective and descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Oncologic dogs were reported to have a lower QoL than healthy dogs, and such data agree with previous literature on the topic [ 18 , 19 ]. The assessment of QoL in the oncologic patient is important to decide and modulate therapeutic choices [ 28 ] as well as to understand the effects of disease and treatment on the animal [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Oncologic dogs were reported to have a lower QoL than healthy dogs, and such data agree with previous literature on the topic [ 18 , 19 ]. The assessment of QoL in the oncologic patient is important to decide and modulate therapeutic choices [ 28 ] as well as to understand the effects of disease and treatment on the animal [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…The comparison with oncologic patients, on the other hand, provided rather unexpected results. In fact, the control group of oncological dogs was recruited as the impact of oncological disease on patients’ QoL, including canine patients, is well-recognized [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies had been dedicated to the quality of life of the chemo-patient, through owners' perception. [11,13,[21][22][23][24] In our study, through the owner's answers of the questionnaire, we concluded that life quality of the patients with canine lymphoma that received chemotherapy was not impaired, and even improved in most of them. The general positive impression given by the owners indicates that chemotherapy is relevant and worthwhile in dogs with lymphoma.…”
Section: Discussionmentioning
confidence: 81%